2022
DOI: 10.1049/smt2.12136
|View full text |Cite
|
Sign up to set email alerts
|

Bubble migration characteristics in power transformer oil under coupled stresses of forced vibration and electrical field

Abstract: The stresses existing in power transformers lead to the generation of bubbles. They are the primary source that worsens and leads to insulation failure. Due to the complexity of bubble dynamics, it is challenging to figure out bubble mechanisms. However, creation, migration, and accumulation mechanisms require further explanation. A set of experiments has been conducted to provide a scientific overview of bubbles. The results revealed that buoyancy is dominant in low electric fields, while high electric fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Building upon the previous findings, Ladislas investigated the migration characteristics of bubbles in oil under the coupling effects of electric and the vibration fields, considering the influence of vibration field on bubble motion and deformation. The findings demonstrated that under the combined action of AC stress and vibration stress, bubbles undergo simultaneous stretching and oscillatory behavior, resulting in an intensified level of bubble distortion [9]. Previous studies have primarily focused on the generation, aggregation, deformation, and motion characteristics of bubbles in liquid phases within a homogeneous electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon the previous findings, Ladislas investigated the migration characteristics of bubbles in oil under the coupling effects of electric and the vibration fields, considering the influence of vibration field on bubble motion and deformation. The findings demonstrated that under the combined action of AC stress and vibration stress, bubbles undergo simultaneous stretching and oscillatory behavior, resulting in an intensified level of bubble distortion [9]. Previous studies have primarily focused on the generation, aggregation, deformation, and motion characteristics of bubbles in liquid phases within a homogeneous electric field.…”
Section: Introductionmentioning
confidence: 99%